2009
DOI: 10.1097/ccm.0b013e31818727bf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intra-aortic balloon counterpulsation in a model of septic shock*

Abstract: Background-Fluid refractory septic shock can develop into a hypodynamic cardiovascular state in both children and adults. Despite management of these patients with empiric inotropic therapy (with or without a vasodilator), mortality remains high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
10
0
3
Order By: Relevance
“…The protocol followed in these experiments has been previously described (20, 21, 23) (Figure 1 and Supplementary Methods). At time 0 (T0), baseline blood samples and hemodynamic profiles were obtained (Supplementary Methods), and then animals received an inoculation of S. aureus (1.5 – 7.5 × 10 9 cfu/kg) into the right caudal lobe via bronchoscopy(20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol followed in these experiments has been previously described (20, 21, 23) (Figure 1 and Supplementary Methods). At time 0 (T0), baseline blood samples and hemodynamic profiles were obtained (Supplementary Methods), and then animals received an inoculation of S. aureus (1.5 – 7.5 × 10 9 cfu/kg) into the right caudal lobe via bronchoscopy(20).…”
Section: Methodsmentioning
confidence: 99%
“…Using intrapulmonary challenges of Staphylococcus aureus to produce septic shock in canines (20, 21), stress doses of dexamethasone (DEX), a specific glucocorticoid agonist, or desoxycorticosterone (DOC), a specific mineralocorticoid agonist, were compared for effects on pathophysiology and survival. To simulate therapeutic interventions commonly employed in human septic shock, animals were managed with standardized sedation, antibiotic therapy, mechanical ventilation support adjusted to correct gas exchange abnormalities, and need-based cardiovascular support using vasopressors and fluids to normalize intravascular pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-aortic balloon pumping (IABP) is expected to increase the cardiac output and reduce the dosage of a vasopressor. Solomon et al demonstrated that in a canine model of severe septic shock with a low cardiac index, IABP prolongs survival time and lowers vasopressor requirements [ 52 ]. Nakamura et al reported two cases of severe sepsis-induced cardiomyopathy with refractory shock [ 53 ].…”
Section: Reviewmentioning
confidence: 99%
“…Healthy canine kidney tissue was provided by the National Institutes of Health (NIH) Division of Veterinary Services. Kidneys were obtained from a healthy 2-year-old male Beagle (Charles River Laboratories, Frederick, MD) used in an Institutional Animal Care and Use Committee (IACUC)-approved study of the effects of intra-aortic balloon counterpulsation on septic shock (Solomon et al 2009 ). Histopathological evaluation of formalin-fixed tissue sections from the specimen was unremarkable.…”
Section: Methodsmentioning
confidence: 99%